Interobserver Agreement in Vascular Invasion Scoring and the Added Value of Immunohistochemistry for Vascular Markers to Predict Disease Relapse in Stage I Testicular Nonseminomas. (December 2019) - Lobo, João; Stoop, Hans; Gillis, Ad J.M.; Looijenga, Leendert H.J.; Oosterhuis, Wolter
Abstract : Vascular invasion has been identified as an informative risk factor for relapse in stage I testicular nonseminomas, used to tailor treatment. We investigated interobserver agreement in vascular invasion reporting and studied the potential additional value of immunohistochemistry for vascular markers for predicting relapse. Patients (n=52) with stage I testicular nonseminomas undergoing surveillance (1993-2006) were included (median follow-up of 66 mo). Two formalin-fixed paraffin-embedded blocks with >1 cm 2 tissue and tumor/normal parenchyma interface were stained with hematoxylin and eosin and CD31, FVIII, and D2-40. Slides were assessed by 3 independent testicular germ cell tumor-dedicated pathologists, and agreement was assessed using Cohen κ statistic. Sensitivity, specificity, and accuracy of vascular invasion scoring in predicting relapse were calculated. Agreement among testicular germ cell tumor-dedicated pathologists was moderate (κ=0.49 to 0.54), as was performance in predicting disease relapse (particularly, specificity of 86%). Immunohistochemistry increased overall sensitivity (71%), but decreased specificity (71%) in predicting relapse. All patients (n=8) with both blood and lymphatic vascular invasion developed a relapse. In multivariable analysis (including age, tumor size, rete testis invasion, and serum tumor markers), only vascular invasion had an independent impact in predicting relapse. Assessment of vascular invasion by testicular germ cell tumor-dedicated pathologists is good and is clinically meaningful, predicting disease relapse. Immunohistochemistry for vascular markers improves sensitivity of detecting disease relapse and allows for the identification of high-risk patients with both blood and lymphatic vascular invasion simultaneously, potentially of interest for tailored chemotherapy. Abstract : Supplemental Digital Content is available in the text.